ANALISIS PERBANDINGAN FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN DAN SPRINGATE PADA SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - REIN ADRIAN KADIR; EKA ZAHRA SOLIKAHAN; NURHAYATI OLII (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2022)
This study aims to find whether or not the difference is between the Altman and Springate methods in the prediction of financial distress and to analyze the level of accuracy of the two methods in the transportation sub-sector. The population in this study employs the transportation of sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique is purposive sampling, with a total sample of 27 companies in the 2016-2020 period. The data analysis technique applies the paired sample t-test and the accuracy test of the prediction method. The results of this study indicate that there is no difference between the Altman and Springate methods in predicting financial distress. However, the Springate method has the highest level of accuracy compared to the Altman method.